The new gap between Iran and the West: The presidential election as an expression of a fundamental shifting of power - Johannes Reissner (Stiftung Wissenschaft und Politik (SWP), 2005)
The outcome of the presidential election in June 2005 was indicative of fundamental social and political developments in Iran 26 years after its Revolution. The surprise victory by populist neo-Conservative Mahmoud Ahmadinejad reflected resentment amongst poorer Iranians. Moreover, a younger generation of politicians whose politics were primarily shaped during their country's eight-year war against Iraq (1980-1988) has now become the tone-setting political class, including in government. Self-assurance is the new credo, and by no means just for those who won the election. Inspired by China's example, Iran is determined to use its wealth of energy resources to go its own way without bowing to the imperious West. But this does not necessarily imply anti-Western politics. Instead, Iran may assertively distance itself from the West and either make clear demands or give the cold shoulder, as it sees fit. (SWP Comments / SWP)
Keywords: 320